The employment of q-PCR using specific primer targeting on mitochondrial cytochrome-b gene for identification of wild boar meat in meatball samples - Ganea Qorry Aina; Yuny Erwanto; Motalib Hossain; Mohd Rafie Johan; Md. Eaqub Ali; Abdul Rohman (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this study was to employ real-time or quantitative polymerase chain reaction (q-PCR) using novel species specific primer (SSP) targeting on mitochondrial cytochrome-b of wild boar species (CYTBWB2-wb) gene for the identification of non-halal meat of wild boar meat (WBM) in meatball products. Materials and Methods: The novel SSP of CYTBWB2-wb was designed by our group using PRIMERQUEST and NCBI software. DNA was extracted using propanol-chloroform-isoamyl alcohol method. The designed SSP was further subjected for validation protocols using DNA isolated from fresh meat and from meatball, which include specificity test, determination of efficiency, limit of detection and repeatability, and application of developed method for analysis of commercially meatball samples Results: The results showed that CYTBWB2-wb was specific to wild boar species against other animal species with optimized annealing temperature of 59°C. The efficiency of q-PCR obtained was 91.9% which is acceptable according to the Codex Allimentarius Commission (2010). DNA, with as low as 5 pg/μl, could be detected using q-PCR with primer of CYTBWB2-wb. The developed method was also used for DNA analysis extracted from meatball samples commercially available. Conclusion: q-PCR using CYTBWB2-wb primers targeting on mitochondrial cytochrome-b gene (forward: CGG TTC CCT CTT AGG CAT TT; Reverse: GGA TGA ACA GGC AGA TGA AGA) can be fruitfully used for the analysis of WBM in commercial meatball samples. [J Adv Vet Anim Res 2019; 6(3.000): 300-307]